Diagnosis and treatment of disorders of intracranial pressure: consensus statement of the Spanish Society of Neurology’s Headache Study Group - J. García-Ull; N. González-García; M. Torres-Ferrús; D. García-Azorín; I.F.J. Molina-Martínez; I. Beltrán-Blasco; S. Santos-Lasaosa; G. Latorre; A.B. Gago-Veiga; J.M. Láinez; J. Porta-Etessam; C. Nieves-Castellanos; et al. (Neurología (English Edition))
Primary intracranial pressure disorders include idiopathic intracranial hypertension and spontaneous intracranial hypotension. Remarkable advances have been made in the diagnosis and treatment of these 2entities in recent years. Therefore, the Spanish Society of Neurology's Headache Study Group (GECSEN) deemed it necessary to prepare this consensus statement, including diagnostic and therapeutic algorithms to facilitate and improve the management of these disorders in clinical practice.This document was created by a committee of experts belonging to GECSEN, and is based on a systematic review of the literature, incorporating the experience of the participants, and establishes practical recommendations with levels of evidence and grades of recommendation. Resumen: Los trastornos primarios de la presión intracraneal incluyen la hipertensión intracraneal idiopática y la hipotensión intracraneal espontánea. El diagnóstico y tratamiento de ambas entidades ha presentado un avance destacable en los últimos años; por lo que desde el Grupo de Estudio de Cefaleas de la Sociedad Española de Neurología (GECSEN) consideramos necesaria la elaboración de este documento de consenso con la inclusión de algoritmos diagnósticos y terapéuticos para mejorar su manejo en la práctica diaria.Este documento ha sido redactado por un comité de expertos del GECSEN tras realizar una revisión sistemática de la bibliografía, incorporando la experiencia de los participantes y estableciendo unas recomendaciones prácticas con niveles de evidencia y grados de recomendación.